Determinar el nivel de presión arterial en estudiantes del bachillerato de la Unidad Educativa Atahualpa del año 2014 - Loayza Sivisapa, Liliana E. (2014)
Obesity has become the epidemic of the XXI century. The incidence and prevalence of hypertension in the early stages of life has increased considerably in undeveloped countries. Both diseases are becoming increasingly important in the early stages of life: It was therefore decided to make a descriptive study to determine the presence of obesity and overweight and hypertension in student’s baccalaureate Education Unit Atahualpa likewise establish the association between the two conditions.